Afiloforales de Colombia III: Amauriderma (Basidiomycetes: Ganodermataceae) en el Herbario Nacional Colombiano - Henao M. Luis Guillermo (Caldasia)
Eight species of Amauroderma have been recorded from Colombia. A. faeulum and A. tapetellum are new species. The examined species are described and brief comments of characters currently used in the taxonomy of the genus are given. Ocho especies de amauroderma han sido registradas para Colombia. A (seulum y A. tapetellum se describen como nuevas especies para la ciencia, y amplía la distribución de tres (A. axile, A. praetervisum, A. sehomburgkii f. sehomburgkil) dentro del pars. Se da una descripción detallada de los especímenes examinados. Las características utilizadas en la sistemática del género se discuten brevemente.